Design of SERENA-6, a phase III switching trial of camizestrant in ESR1 -mutant breast cancer during first-line treatment - Nicholas C. Turner; Cynthia Huang Bartlett; Kevin Kalinsky; Massimo Cristofanilli; Giampaolo Bianchini; Stephen Chia; Hiroji Iwata; Wolfgang Janni; X. Cynthia; Erica L. Mayer; Yeon Hee Park; Stephen B. Fox; et al. (2023)
ESR1 mutation (ESR1m) is a frequent cause of acquired resistance to aromatase inhibitor (AI) plus cyclin-dependent kinase 4 and 6 inhibitors (CDK4/6i), which is a first-line therapy for hormone-receptor-positive (HR+)/human epidermal growth factor receptor 2-negative (HER2-) advanced breast cancer (ABC). Camizestrant is a next-generation oral selective estrogen receptor degrader (SERD) that in a phase II study significantly improved progression-free survival (PFS) over fulvestrant (also a SERD) in ER+/HER2- ABC. SERENA-6 (NCT04964934) is a randomized, double-blind, phase III study evaluating the efficacy and safety of switching from an AI to camizestrant, while maintaining the same CDK4/6i, upon detection of ESR1m in circulating tumor DNA before clinical disease progression on first-line therapy for HR+/HER2- ABC. The aim is to treat ESR1m clones and extend the duration of control of ER-driven tumor growth, delaying the need for chemotherapy. The primary end point is PFS; secondary end points include chemotherapy-free survival, time to second progression event (PFS2), overall survival, patient-reported outcomes and safety.